The Position of Convict as Justice Collaborator in Revealing Organized Crime - Bambang Sugiri; Nurini Aprilianda; Hanif Hartadi (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2021)
This article aims to examine the position of the convict as justice collaborator in revealing organized crime. A justice collaborator can assist law enforcement officers. The background of the study is the concept of crown witness, which is often used in proving criminal cases, even though it violates human rights. A difficulty in revealing organized crime is that perpetrators mostly do not disclose their criminal network and the parties involved. Information from the convict related to the network of the crime they committed makes law enforcement officers easier to reveal the organized crime. This study used a juridical analysis with an approach to laws and regulations, conceptual method, and comparative method. The results of the study show that convict who chose to become a justice collaborator has a vital role. Law enforcement officers can take advantage of this role in exposing organized crimes without human rights violations to the convict. The convict can have a reward in the form of parole and additional remissions.Kedudukan Narapidana sebagai Justice Collaborator dalam Pengungkapan Kejahatan TerorganisirAbstrakArtikel ini bertujuan mengkaji kedudukan narapidana sebagai justice collaborator dalam pengungkapan kejahatan terorganisir yang dapat membantu tugas aparat penegak hukum. Hal ini dilatarbelakangi konsep saksi mahkota yang sering dipergunakan dalam pembuktian perkara pidana namun dinilai melanggar HAM. Kesulitan pengungkapan kejahatan teroganisir adalah para pelaku yang terlibat tidak mengungkapkan jaringan kejahatannya serta pihak yang terlibat.  Informasi dari narapidana terkait jaringan kejahatan yang pernah dilakukannya, memudahkan pengungkapan kejahatan terorganisir oleh aparat penegak hukum. Pada penulisan ini penyusunan dilakukan dari hasil analisis yuridis melalui sebuah pendekatan peraturan-peraturan undang-undang, metode konseptual dan juga mempergunakan metode perbandingan. Adapun hasil dari penelitian memperlihatkan bahwa narapidana sebagai justice collaborator memiliki peran yang dapat dimanfaatkan oleh aparat penegak hukum dalam mengungkap kejahatan terorganisir tanpa dinilai melakukan pelanggaran HAM kepada narapidana karena adanya pemberian penghargaan berupa pembebasan bersyarat dan remisi tambahan.Kata Kunci: justice collaborator, kejahatan terorganisir, narapidana.DOI: https://doi.org/10.22304/pjih.v8n2.a5